ALASAN GURU TIDAK MENGGUNAKAN MEDIA BERBASIS TEKNOLOGI DI SMP DWIPAABADIKECAMATAN KATEMAN KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - Rissa Mardika; Inoki Ulma Tiara; Waza Karia Akbar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning media is one of the tools used by teachers to facilitate the teaching and learning process in schools. However, there are still some teachers who have not or cannot use learning media optimally as a tool to facilitate the learning process. The purpose of this study is to describe "Teacher obstacles in the use of learning media at SMP DWIPAABADI. The theory used in this study is the behaviorist theory. In this study, the method used is the qualitative method. Data collection techniques used are observation, in-depth interviews, and document studies. The unit of analysis in the study is the group. Data analysis uses the Miles and Huberman model, namely data collection, data reduction, data presentation, and drawing conclusions. This study uses a qualitative approach. The informants of this study are teachers who have obstacles to the use of learning media. The technique used in determining the informants for this study is using the Purposive Sampling technique, namely the type of non-probability sample or determined by the researcher himself. Data collection techniques using interview and documentation methods. The validity of the data uses triangulation. The results of this study indicate that there are several obstacles faced by teachers in using learning media, namely: 1) Low teacher knowledge of learning media, 2) Teachers are not creative in making media, 3) Limited time to understand learning media, 4) Feeling comfortable with other methods.